Applications, impacts, and management of biochar persistent free radicals: A review - Zhang, Ruirui; Zhang, Ruiling; Zimmerman, Andrew R.; Wang, Hailong; Gao, Bin (Environmental pollution (1987), 2023)
Biochar is a promising environmental contaminant remediation agent because of its adsorptive and catalytic properties. However, the environmental effects of persistent free radicals (PFRs) produced by biomass pyrolysis (biochar production) are still poorly understood, though they have received increasing research attention in recent years. Although PFRs both directly and indirectly mediate biochar's removal of environmental pollutants, they also have the potential to cause ecological damage. In order to support and sustain biochar applications, effective strategies are needed to control the negative effects of biochar PFRs. Yet, there has been no systematic evaluation of the environmental behavior, risks, or management techniques of biochar PFRs. Thus, this review: 1) outlines the formation mechanisms and types of biochar PFRs, 2) evaluates their environmental applications and potential risks, 3) summarizes their environmental migration and transformation, and 4) explores effective management strategies for biochar PFRs during both production and application phases. Finally, future research directions are recommended. [Display omitted] •Formation mechanisms and types of biochar Persistent Free Radicals (PFRs) are outlined.•Environmental applications and risks of biochar PFRs are evaluated.•Environmental migration and transformation of biochar PFRs are summarized.•Management of biochar PFRs during both production and application phases are explored.